1988
DOI: 10.1007/bf01649680
|View full text |Cite
|
Sign up to set email alerts
|

Single-layer anastomosis in surgery of the large bowel

Abstract: A prospective study was undertaken to evaluate the results of a single layer appositional technique for large bowel anastomoses used in a University Hospital. 316 patients were entered during an 18-month period. Anastomoses were situated within the peritoneal cavity in 277 patients and below the peritoneal reflection in 39. No covering stoma was made. The incidence of clinical leakage was 1.6% and of wound infection 1.9%. These results compare favourably with those obtained by stapling. For intraperitoneal ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A Swiss muiticenter prospective study showed a rate of only 0.3% clinical leakage for 586 strictly intraperitoneal colon anastomoses [8]. Similar results have recently been published by other investigators [9,10].' A grow- In gastric surgery, clinical experience with single-layer continuous suture is not well documented.…”
mentioning
confidence: 60%
“…A Swiss muiticenter prospective study showed a rate of only 0.3% clinical leakage for 586 strictly intraperitoneal colon anastomoses [8]. Similar results have recently been published by other investigators [9,10].' A grow- In gastric surgery, clinical experience with single-layer continuous suture is not well documented.…”
mentioning
confidence: 60%